THE INFLUENCE OF MOVIE TOWARD TO STUDENTS’ WRITING SKILL NARRATIVE TEXT - Yaser Arafat (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Banten, 2021)
The background of the study in this research is based on the phonemena that student have difficulty in writing narrative text. Students could not describing thing, place, and person detail because the student don’t have ideas when they are asked to describe thing, place and person. So they need some ways, method or aids which could help them in writing narrative text. Movie media is one of ways that can be used in teaching writing descriptive text. The problem of this research can be stated that how is the implementation influence of movie toward to students’ writing skill narrative text. Its purpose are firstly to know the improvement of students ability in writing skill narrative text. The second is to find out how the use the movie contributes to student improvement in writing skill narrative text. So student are more active and interested in learning writing activities in class, especially the are happy with the application of learning methods to improve their writing skill by using Movie.